A chorus line [videorecording (DVD)] - Attenborough, Richard; Douglas, Michael, 1944-; Reed, Alyson; Mann, Terrence; Bennett, Michael, 1943-1987 (MGM Home Entertainment, 2003)
In preparation for a Broadway musical, a group of aspiring stage performers is put through their paces by a veteran stage director using some singular techniques.